Cell-free Chromatin Immunoprecipitation (cfChIP) from blood plasma can determine gene-expression in tumors from non-small-cell lung cancer patients. (September 2020) - Vad-Nielsen, Johan; Meldgaard, Peter; Sorensen, Boe Sandahl; Nielsen, Anders Lade
Highlights: NSCLC patient blood plasma harbors tumor derived nucleosomes. Blood plasma nucleosomes have maintained the tumor H3K36Me3 modification profile. Blood plasma nucleosome H3K36Me3 levels and tumor gene expression levels correlate. cfChIP can quantify H3K36Me3 over gene specific loci in blood plasma nucleosomes. cfChIP can quantify tumor gene expression levels using NSCLC patient blood plasma. Abstract: Objectives: Lung cancer is the leading cause of cancer related death worldwide. Accurate molecular diagnostics from a tumor biopsy is paramount for correct diagnosis, treatment strategy, and prediction of outcome. However, a tumor biopsy can be misleading due to tumor heterogeneity and consecutive biopsies are rarely achievable. Importantly, tumor-specific genetic information concerning mutations and translocations, can also be obtained from liquid biopsies, e.g. blood plasma, containing cell-free DNA (cfDNA) with both systemic and tumor origin. Tumor-specific gene-expression information can also be determined from liquid biopsies using cfDNA methylation and cell-free RNA analyses. However, supplementary methodologies that can determine gene-expression patterns in lung tumors from liquid biopsies could also have diagnostic impact. Materials and methods: We here present the method cell-free chromatin Immunoprecipitation (cfChIP), which for genes having high expression specifically in the tumor, can determine such gene-expression from blood plasma. In cfChIP cell-free nucleosomes modified with histone H3 lysine 36 tri-methylation (H3K36me3), a mark quantitatively correlated with the transcription of the underlying gene, are isolated, and associated cfDNA quantified. Results: We demonstrate that cfChIP from lung cancer patient blood plasma can successfully quantify the level of H3K36me3 associated with circulating cell-free nucleosomes and thereby quantify the transcriptional level of genes associated with these nucleosomes. Moreover, as a proof-of-principle we show that in blood plasma from 14 lung cancer patients, H3K36me3 cfChIP can replicate the expected higher expression of KRT6 in lung squamous cell carcinoma relative to adenocarcinoma. Conclusion: This work shows that for genes with a high expression specifically in tumor, cfChIP can determine this gene-expression pattern from blood plasma. cfChIP is a method that determine gene-expression at the transcriptional level and accordingly can supplement cfDNA methylation and cell-free RNA analyses.